Seção Técnica de Triagem, Emergência e Documentação –STTED - Tutumi, Amélia Miyuki Nagamatsu; Damaceno, Ana Lucia Francischini; Leite, Ariana Celis; Saito, Celia Tomiko Matida Hamata; Kanno, Cláudia Misue; Almeida, Daniel Augusto de Faria; Cruz, Dayane da; Teodoro, Dulcinea Aparecida; Costa, Edna Maria Vieira; Navega, Eliseide Maria Ferreira Silva; França, Graziela Piva D'angelo de; Silva, Ivete Mariko Yokote Castro; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Ariana Celis Leite Celia Tomiko Matida Hamata Saito Eliseide Maria Ferreira Silva Navega